If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + w + 6 + w + 6 + w = 92 Reorder the terms: 6 + 6 + w + w + w + w = 92 Combine like terms: 6 + 6 = 12 12 + w + w + w + w = 92 Combine like terms: w + w = 2w 12 + 2w + w + w = 92 Combine like terms: 2w + w = 3w 12 + 3w + w = 92 Combine like terms: 3w + w = 4w 12 + 4w = 92 Solving 12 + 4w = 92 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4w = 92 + -12 Combine like terms: 12 + -12 = 0 0 + 4w = 92 + -12 4w = 92 + -12 Combine like terms: 92 + -12 = 80 4w = 80 Divide each side by '4'. w = 20 Simplifying w = 20
| 2m^3-50m=0 | | 97-16x=-63 | | -4(6+7r)=-r+30 | | -6(4b+7)=-4(6b-7) | | 4(1x-6)+6=6x-8 | | 6x-1=9x-10 | | 7x+4=3x-52 | | 1r-10=10r+8 | | 4+6(k-8)=8k-38 | | 8-(-16)= | | x^3+5x^2+x^2-5x-12x-60=0 | | 5x(6-3)= | | 4w+5w=51 | | 10(8m+9)=10(6m-3) | | 8x+-8y=5 | | X-366=415 | | -5x+9=2x-4 | | x+3x+54+2x=180 | | 8p-8=8(-6p-8) | | 2x-6x+4=-12 | | 6x^2-8x-11=0 | | 4m^2-36m= | | x(3x+54)(2x)=180 | | 31=9t-13t+7 | | 19-13p=17p-8 | | (-3n+5)(-5.7)= | | 1.5+.3(h-6)=.8h+2 | | -[6x-(3x+5)]=-4-[4(2x-4)-3x] | | 37+3n=-2 | | (5y-4)(6y-7)= | | 5+2k=3k-3 | | (-8x^4+6x+3)+(2x^4-2x^2+7)= |